PENINGKATAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN TENTANG PROSES PEMILIHAN UMUM MELALUI MODEL PEMBELAJARAN EXAMPLES NON EXAMPLES SISWA KELAS VI SDN KUTUWETAN KECAMATAN JETIS KABUPATEN PONOROGO - Tukirah, Tukirah (Educatio Vitae, 2016)
The research entitled “The Improvement of The Results of The Study of Citizenship Education in The Topic of General Election Process through The Learning Model of Examples Non Examples of The Sixth Graders of Kutuwetan State Primary School of Jetis Ponorogo in Semester I 2013-2014 Academic Year” is a class act research towards 16 students which is conducted in 3 cycles consisting of 6 meetings. Each meeting consists of 2 X 35 minutes. Every cycle includes the activities of planning, implementation, observation, and reflection. The data are taken by using test instruments, interviewing, distributing questionnaires and journals. The aim of the research is to know the improvement of the student achievement. The learning model of Examples Non Examples is proven to be able to improve the learning competence which is noticed by the improvement of mean score in which it is 74.38 in cycle I; 78.13 in cycle II; and 80.63 in cycle III. Beside that, there is also the percentage improvement of the learning accomplishment in which the percentage is 62.50% in cycle I, 87.50% in cycle II and 100% in cycle III. The research proves that the use of the learning model of Examples Non Examples in the process of learning is capable to improve the learning competence and the results of the study in citizenship education subject, especially in “explaining the process of general election and the process of the election of the head of the region.” Key Words: Competence, Examples Non Examples, Citizenship Education